Amorphous‐TiO2‐Encapsulated CsPbBr3 Nanocrystal Composite Photocatalyst with Enhanced Charge Separation and CO2 Fixation. Issue 22 (11th September 2018) - Xu, Yang‐Fan; Wang, Xu‐Dong; Liao, Jin‐Feng; Chen, Bai‐Xue; Chen, Hong‐Yan; Kuang, Dai‐Bin
Abstract: Artificially photocatalytic reduction of CO2 into valuable chemicals, responding to the call of carbon neutral economy, has aroused considerable interests so far. Among those photocatalysts screened, an emerging and promising alternative of inorganic CsPbBr3 perovskite has recently been reported. Here, to attain preferable photocatalytic performance, an amorphous‐TiO2 ‐encapsulated CsPbBr3 nanocrystal (CsPbBr3 NC/a‐TiO2 ) hybrid is demonstrated through a solution processing strategy. After optimizing the a‐TiO2 matrix amount by tuning the tetrabutyl titanate precursor volume, the CsPbBr3 NC/a‐TiO2 composite exhibits a marvelous 6.5‐fold improvement on the consumption of photoelectrons in photocatalytic CO2 reduction reaction when compared with the individual CsPbBr3 NC. Such significant enhancement is ascribed to the accelerated electron–hole separation and the multiplied CO2 adsorption. Thus, as an available prototype, this work offers a rational encapsulation design for efficient halide perovskite photocatalyst. Abstract : A newly designed amorphous‐TiO2 ‐encapsulated CsPbBr3 nanocrystal is prepared for photocatalytic CO2 reduction reaction, leading to a maximum 6.5‐fold increment on electron consumption by quenching the radiative recombination and increasing CO2 feedstock adsorption. This study emphasizes the pivotal issues in designing halide perovskite photocatalyst and its solution by composite material concept.